The Effect of Materialism and Hedonic Shopping Toward Impulse Buying of Muslim Consumer: A Moderating Role of Religiosity - Rusanti, Ega; Yuningsih M., A. Alfira; Kamil, Muhammad Ahsan (IQTISHADIA, 2024)
This paper aims to explore the extent to which matrealism and hedonic shopping behavior encourage Muslim consumers to make impulse purchases with the role of religiosity as a moderating variable. Convenience sampling was used to collect primary data from 150 general public and structural partial least squares modeling (PLS-SEM) was used to analyze the data. The study find that materialism has a positive and significant effect on impulse buying of Muslim consumers, hedonic has a positive and significant effect on impulse buying of Muslim consumers, religiosity has a negative and insignificant effect on impulse buying of Muslim consumers, while religiosity does not moderate the relationship between materialism and hedonic behavior on impulse buying in Muslim consumers. This research is limited to random respondents with a very small sample. Hence, further research is expected to be able to select a more purposive sample and use other variables that have not been explored more deeply in this study. This paper provides to the renewal of literature on aspects that encourage impulsive buying behavior, namely hedonic shopping and materialism and religiosity which also plays a role in moderating consumers in suppressing impulsive buying decisions of Muslim consumers in Indonesia.